Implementation of Blue Ocean Strategy in eCommerce: Case Study Among Arabic Investors in Malaysia - Najwani Shahidan, Athifah; Abumandil, Mohanads; Abd Halim, Mutiasobihah (International Journal of Psychosocial Rehabilitation, 2020)
E-commerce was potentially extending firms’ competency and efficiency. Hence, Arabic investors in Malaysia had a serious target to increase the usage of this technology. However, the implementation of e-commerce among Arabic investors was still limited due to the lack of trust while dealing with it. Consequently, extensive efforts have been made to further understand this issue. To appear more insightful, this study develops a research model utilizing the technological and organizational factors to identify the determinants of the firms’ propensity in implementing e-commerce. In addition, this study hypothesizes that partnership characteristics—trust and dependency—act as moderators between the variables of implementation e-commerce. A total of 323 questionnaires were self-administrated by Arabic investors in Malaysia in 205 firms that were registered in the large capital of Malaysia and were analyzed using the partial least squares approach. The results revealed that marketing and purchasing departments have had different views regarding the determinants of adoption. Moreover, the results showed that the moderating role of trust was less pronounced. These findings have demonstrated how dependence asymmetries between trading partners may change the adoption motivations. The importance of considering the views and opinions of business partners for the adoption is further explained in this study.